PENGARUH KEPERCAYAAN, KEMUDAHAN, DAN KUALITAS INFORMASI PADA WEBSITE WWW.LAROSLAPTOP.COM TERHADAP KEPUTUSAN PEMBELIAN ONLINE - Raden Bagus Rendy Putra Pradwita; Yunus Handoko; Ike Kusdyah Rachmawati (Jurnal Apresiasi Ekonomi, 2020)
Online shopping in Indonesia especially in the city of Malang is experiencing very rapid development, this is used by entrepreneurs to sell their wares via the internet. Some entrepreneurs use the use of websites to market their merchandise online. Sales through the website will be successful if consumers have a high level of trust in the website, and consumers get the ease and quality of information needed when shopping online at the intended online shopping website. This study aims to determine the effect of trust, convenience, and quality of information on the website www.laroslaptop.com on online purchasing decisions. The subjects in this study were consumers from Malang who had made online purchases on the website www.laroslaptop.com in 2018 with a sample of 100 respondents. Data collection techniques using observation, documentation, questionnaires, and interviews. The sampling method uses Simple Random Sampling. The method of data analysis uses multiple linear regression analysis with tools such as Excel software and SPSS IBM Statistics ver. 26.  The results of this study indicate that trust, convenience, and quality of information partially have no effect on online purchasing decisions. And simultaneously found a significant influence between trust, convenience, and quality of information on online purchasing decisions. Keywords: Trust, Ease, Quality of Information, Online Purchasing Decisions.